UPAYA GURU DALAM MENANAMKAN KEDISIPLINAN SANTRI DI PONDOK PESANTREN ISLAMIC CENTER BIN BAZ YOGYAKARTA - Teguh, Teguh; Rabbani, Muzhaffar Aiman; Ihsan, Ahmad Siyam Al; Saputra, M Ikhsan; Sugari, Dedi; Permadi, Muhammad Arrafi Muzhaffar; Sulisno, Sarwadi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
His study aims to describe and analyze teachers’ efforts in instilling the value of discipline among students at Pondok Pesantren Islamic Center Bin Baz Yogyakarta. The research employed a descriptive qualitative approach using observation, interviews, and documentation as data collection techniques. The collected data were analyzed interactively through reduction, presentation, and conclusion drawing stages. The findings reveal that the cultivation of discipline in the pesantren is carried out through three main approaches: habituation, exemplary modeling, and supervision. Habituation is implemented through structured daily routines, exemplary modeling is shown by teachers and dormitory mentors through direct behavior, and supervision ensures consistency and rule enforcement. The religious environment, teacher role models, and collective supervision system significantly reinforce the formation of students’ disciplinary character. The novelty of this study lies in the integration of these three approaches within a single educational system that emphasizes not only rule compliance but also moral and spiritual awareness of discipline among students.